Pengalaman Pelanggan sebagai Mediator Value Co-Creation dan Kepercayaan Pelanggan pada Kopi Kenangan - Andhy, Andhy Tri Adriyanto; Galuh, Galuh Wulansari (PT. Syalma Global Solution, 2026)
The development of the modern coffee shop industry in Indonesia requires companies to build customer trust through active involvement and positive experiences. This study aims to analyze the effect of Value Co-Creation on Customer Trust with Customer Experience as a mediating variable on Kopi Kenangan consumers in Semarang City. The study used a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method on 148 respondents selected through purposive sampling. The results show that Value Co-Creation has a positive and significant effect on Customer Experience and Customer Trust. Customer Experience has a positive and significant effect on Customer Trust. Customer Experience partially mediates the effect of Value Co-Creation on Customer Trust. This study confirms that consumer involvement in the service process not only directly builds trust, but also through the formation of positive experiences that strengthen the perception of the company's reliability and commitment. Thus, Customer Experience plays an important role as a mechanism that connects consumer engagement with the formation of trust in the brand.